The INSEN Experience, by INSEN Chairs - Tariq Majeed; Jason Timothy Harris; Oum Keltoum Hakam; James Larkin; Şebnem Udum; Johannes H Sterba (International Journal of Nuclear Security, 2020)
As a feature of this issue, we asked INSEN chairs to share their thoughts about what the organization has meant to them as they led this network of colleagues in the mission of improving nuclear security education and training at institutions and organizations around the world. Below are their stories. The chairs describe their paths to INSEN leadership, the organization’s work, challenges, and successes, and how the experience of leading INSEN affected their professional and personal lives. IJNS thanks each of the authors contributing to this collaborative article. Every chair has done a tremendous job in their tenure as INSEN’s leader—and we, the membership and all who have benefitted from their dedication and expertise, are deeply grateful. We look forward to INSEN’s next decade under the leadership of colleagues and friends like these.